Plasmon-triggered living photopolymerization for elaboration of hybrid polymer/metal nanoparticles. (November 2020) - Kameche, Farid; Heni, Wajdi; Telitel, Siham; Ge, Dandan; Vidal, Loïc; Dumur, Frédéric; Gigmes, Didier; Lalevée, Jacques; Marguet, Sylvie; Douillard, Ludovic; Fiorini-Debuisschert, Céline; Bachelot, Renaud; et al.
Graphical abstract: Abstract: Surface plasmon resonance can be used to manipulate light at the nanoscale. It was used here to trigger photopolymerization of an atom transfer radical polymerization (ATRP) molecular system, leading to a thin polymer shell at the surface of the metal nanostructure. The polymerization can be reactivated from the first polymer shell to covalently graft a second monomer layer with precise control over the thickness at the nanometric scale, depending on the photonic parameters. This route can be applied to different nanoobjects and allows an anisotropic surface modification in agreement with the spatial localization of the enhanced electromagnetic field near the nanostructure. This new route opens the door towards the preparation of multifunctional hybrid metal/polymer nanostructures.